Analysis of potential biology learning resources based on the result of ethnobotanic research on wedding processions in Magelang district - Naim, Darin; Moro, Hendro Kusumo Eko Prasetyo (Universitas Ahmad Dahlan, 2024)
Analysis of Potential Biology Learning Resources Based on The Result of Ethnobotanic Research on Wedding Processions in Magelang district. This research is about the ethnobotany of weddings in the Magelang Regency community to find out the wedding procession and the use of plants and their meaning, the style of wedding traditions and to analyze the potential of biological learning resources based on research results. This research is qualitative research with 5 sources as research subjects. The object of this research is plants used in wedding processions. The data collection techniques used were interviews, observation and documentation using interview and observation guide instruments. The data analysis technique used is descriptive data analysis and analysis of potential biology learning resources. The results of the research show that there are 20 traditional wedding processions in Magelang Regency, although not all people use the 20 processions for financial and practical reasons. There are 25 Spermatophyta plants, all of which are included in Angiospermae. The parts of the plants used in the wedding procession are 13 leaves, 6 stems, 4 seeds, 6 flowers, 3 fruits, and 1 shoot with the largest tribe being Fabaceae, namely, 6 plants. The pattern of wedding traditions in Magelang Regency is more similar to the procession in Surakarta with 17 similar processions. The meaning of all the plants used is the hope that the wedding will run smoothly. Analysis of the research results shows that this research has the potential to be a source of learning biology, but cannot be associated with the Plantae material in KD 3.8 and is more suitable as enrichment material.